New synonymy and redescription of Mastigus deustus (Thunberg) (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2012)
Basing on examination of type specimens and original descriptions, the status of primary types of two South African Mastigini is clarified: i) the type specimen of Mastigus deustus (Thunberg) (originally described in Notoxus), previously incorrectly treated as a holotype, was found to be a syntype; ii) the type specimen of Mastigus glabratus Klug previously treated as a holotype is in fact a syntype; iii) the specimen previously treated as a paratype of M. glabratus is not a primary type. Lectotypes for Notoxus deustus and Mastigus glabratus are designated, and M. glabratus is placed as a junior objective synonym of M. deustus. Mastigus deustus is redescribed, and its diagnostic characters, including the aedeagus, are illustrated.